Measuring metabolic rates of small terrestrial organisms by fluorescence-based closed-system respirometry. - Tomlinson, Sean; Dalziell, Emma; Withers, P.; Lewandrowski, W.; Dixon, Kingsley; Merritt, D. (The Company of Biologists Ltd., 2018)
We explore a recent innovative variation of closed-system respirometry for terrestrial organisms, whereby pO2is repeatedly measured fluorometrically in a constant-volume chamber over multiple time points. We outline a protocol that aligns this technology with the broader literature on aerial respirometry, including the calculations required to accurately convert O2depletion to metabolic rate (MR). We identify a series of assumptions, and sources of error associated with this technique, including thresholds where O2depletion becomes limiting, that impart errors to the calculation and interpretation of MR. Using these adjusted calculations, we found that the resting MR of five species of angiosperm seeds ranged from 0.011 to 0.640 mL.g-1h-1, consistent with published seed MR. This innovative methodology greatly expands the lower size limit of terrestrial organisms that can be measured, and offers the potential for measuring MR changes over time as a result of physiological processes of the organism.